Geographies of Cocaine: Trajectories of Colombian Women Imprisoned for Drug Trafficking in Ecuador - Ana María Cerón Cáceres (Íconos)
This article examines the geography of cocaine through the testimonies of four Colombian women serving time in the Latacunga prison located just south of Quito in Ecuador. The conversations with these women and the ethnography of the visit to the Latacunga prison illustrate how global processes, in this case surrounding the coca economy and the struggle for its control, are embodied in lived experiences. In the testimonies of these women two different geographies of cocaine emerged: one that criminalizes the movement of "suspicious" bodies and rearticulates international borders within the walls of the prison. In contrast, there is another geography that is constituted through the clandestine journeys these women take and in confronting the barriers that this first geography of illegality imposes.